Administrastion Sanctions, Income Level And E-Samsat System On Vehicle Taxpayer Compliance: Administrastion Sanctions, Income Level and E-SAMSAT system on Vehicle Taxpayer Compliance - Sulastri, Evi; Rahma Sari, Intan (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The aim of the study : (1) Determining the impact of administrative sanctions on vehicle taxpayer compliance. (2) Determining the impact of income level on vehicle taxpayer compliance. (3) Determining the impact of E-Samsat system on vehicle taxpayer compliance. The number of samples used in this research was 72 respondents, which was calculated based on the Slovin formula, with the sample determination method being the appropriate sampling method. Data collection was carried out using a questionnaire method and processing was carried out using SPSS Statistics 26.The results of the research that have been carried out state that : (1) Administrative sanctions have a positive effect on motor vehicle taxpayer compliance. (2) Income level does not have a positive effect on motor vehicle taxpayer compliance. (3) The introduction of the E-Samsat system have a positive effect on motor vehicle taxpayer compliance.